Structural features of a novel polysaccharide isolated from a New Zealand Maori mushroom Iliodiction cibarium. (10th April 2015) - Ren, Lu; Edwards, Patrick J.B.; Perera, Conrad O.; Hemar, Yacine
Abstract: A purified water-soluble fraction (ICP5) of a polysaccharide, isolated from a local Maori mushroom Iliodiction cibarium in New Zealand, was investigated for its structural properties. Size exclusion chromatography and dynamic light scattering showed that ICP5 had a large MW of 1.6×10 5 Da with a hydrodynamic diameter of 83±8 nm. Particle size measurements also displayed the tendency of ICP5 to aggregate when suspended in water. The results of GC–MS, FTIR and NMR analyses allowed some characteristics of the chemical structure of ICP5 to be determined. GC–MS results showed that ICP5 contained only glucose (81.61%), galactose (12.90%) and mannose (5.49%) monomers. The characterized fragment structures of ICP5 were found to be dominantly consisting of uronic acids, which formed a backbone containing 1, 4-β-d -Glc p A. A small amount of unsaturated uronic acid also appeared to be present. Graphical abstract: Highlights: A polysaccharide (ICP5) was purified from soluble extracts of a New Zealand local mushroom Iliodiction cibarium . ICP5 is a homogeneous polysaccharide with a large MW of 1.6×10 5 Da and an average particle size of 83±8 nm. ICP5 displayed an ability to aggregate. ICP5 contains a large amount of uronic acids. The fragment structures of ICP5 were characterized to have a backbone that contained a significant proportion of 1, 4-β-d -Glc p A.